Synthesis and Crystal Structure of 1,4-Di(1-naphthyl)-2,5-piperazinedione - Wen, Yong-Hong; Zhang, Shu-Sheng; Yu, Bao-Hui; Liu, Qing; Li, Xue-Mei (Asian Journal of Chemistry, 2010)
The crystal structure of 1,4-di(1-naphthyl)-2,5-piperazinedione has been determined by single crystal X-ray diffraction method. The crystal belongs to monoclinic system, space group C2/c with unit cell constants a=28.71 (2), b=5.721 (4), c=11.451 (9) Å, V=1847 (2) Å3, Z=8, Dc=1.368 g/cm3 μ=0.092mm–1, F(000) = 792, R and wR are 0.0871 and 0.2836, respectively for 1601 unique reflections with 998 observed reflections (I > 2σ(I)). The molecules are interconnected into three-dimensional network by O1W-H1W1…O1 & C8-H8…O1W intermolecular interactions.